2012
DOI: 10.2478/v10059-012-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of interpersonal trust among children and adolescents

Abstract: Development of interpersonal trust among children and adolescentsThe main purpose of the present article is to introduce a topic related to the development of interpersonal trust among children and adolescents. Although this subject, since the beginnings of psychology considered as an academic discipline, has been regarded as an essential component of human functioning, there are still very few theoretical and empirical studies that approach the issue from a developmental point of view. In this paper the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Trust in parents develops during early attachment relationships with caregivers [70,71]. Over numerous interactions in which caregivers make and keep promises, individuals develop an expectation that others will act in trustworthy ways, strengthening their capacity to trust others [72]. Adolescents' ability to form trusting relationships has been linked with their psychosocial adjustment [73][74][75], willingness to share information with their parents [76,77], and attainment of autonomy within the parent-teen relationship [78,79].…”
Section: Parent-teen Trustmentioning
confidence: 99%
“…Trust in parents develops during early attachment relationships with caregivers [70,71]. Over numerous interactions in which caregivers make and keep promises, individuals develop an expectation that others will act in trustworthy ways, strengthening their capacity to trust others [72]. Adolescents' ability to form trusting relationships has been linked with their psychosocial adjustment [73][74][75], willingness to share information with their parents [76,77], and attainment of autonomy within the parent-teen relationship [78,79].…”
Section: Parent-teen Trustmentioning
confidence: 99%
“…General research and theory suggest how trust in a person can facilitate processes that lead to benefits for the trustor (if the person is indeed worthy of trust). Trust increases the trustor's willingness to rely on, receive care from, and be influenced by the person (Banerjee et al, 2006;Szczesniak, Colac ßo, & Rond on, 2012;Watson, 2003). This trust in the person (e.g., in their advice and goodwill) can be especially valuable in helping the trustor deal with situations of vulnerability (Dunn & Schweitzer, 2005;Li, 2007).…”
Section: Literature Review: Why Trust Might Matter Definition and Facmentioning
confidence: 99%
“…The universal patterns of trust identified in the current study, also supported Erikson's (1995) proposition that trust is a key developmental stage. Building on Erikson's theory, Szcześniak, Colaço, and Rondón (2012) argued that children's ability to trust others allows them to deal with new situations with confidence. Similarly, attachment theory suggested that experiencing consistent and dependable caregiving fosters a sense of trust (Bridges, 2003;Mikulincer, 1998) with trust pivotal for the development of secure attachments (Bowlby, 1969).…”
Section: Running Head: Cross-cultural Investigation Of Children's Trustmentioning
confidence: 99%